Eastern Spiritual Practices as a Form of Individual Physical Culture - Zubarev, Alexander (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The paper deals with Eastern spiritual practices that are defined as cultural forms of explicitly foreignculture origin and revealed through their common feature – bodily orientation. Basing on numerous concepts of sociology of the body, sociology of sport, eastern spiritual practices are presented as specific forms of body culture.The empirical base of the analysis was represented by a number of narrative interviews conducted by the author in Kharkov in 2012. It is emphasized that such ideas in the structure of the Eastern spiritual practices like connection of mental and physical states, the concept of life energy, magical connection between alive and dead people, as well as orientation of body techniques to improve health could play a decisive role in the processes of sense-forming of carriers of these practices and become a specific cultural resource in conditions of socio-cultural transformations.